Bir otopsi olgusunda otosomal çekinik Lökodistrofi: Canavan hastalığı - (:unkn) unknown (My University, 2007)
Canavan hastalığı, beyaz cevherin spongiform dejenerasyonu ile kendini gösteren nadir görülen otosomal çekinik (resesif) bir lökodistrofidir. 17. kromozomun kısa kolunda lokalize bir genin mutasyonunun neden olduğu aspartoasiiaz enzim eksikliğinin bu hastalıktan sorumlu olduğu düşünülmektedir. Çalışmamızın amacı, özellikle çocukluk çağında, ani ve şüpheli ölüm nedeni olarak karşımıza çıkabilecek metabolik hastalıklardan biri olan Canavan hastalığında beyinde saptanan morfolojik değişiklikleri, olgunun klinik özellikleri ile birlikte ortaya koymaktır.

Canavan disease is a very rare autosomal recessive leukodistrophy characterized by spongiform degeneration of the white matter. Disease is caused by mutations in the aspartoacylase gene which lead to deficiency of aspartoacylase enzyme activity. The aspartoacylase gene localized on the short arm of chromosome 17. Like all other Leukodystrophies Canavan disease is also considered within the metabolic disorders may cause sudden and unexpected deaths especially in childhood. The aim of our study is to determine morphological changes of this disease.
Canavan disease :An automosal recessive leukodistrophy identified at autopsy
Keywords: Pediatri